Analisis kemampuan berpikir tingkat tinggi peserta didik dalam menyelesaikan LKPD berbasis etnomatematika pada motif kain tenun - Sulfian; Nur Rahmah Alia; Andi Ika Prasasti Abrar; Fitriani Nur (Papanda Journal of Mathematics and Science Research, 2026)
This study aims to analyze students’ Higher Order Thinking Skills (HOTS) in solving ethnomathematics-based student worksheets (LKPD) using woven fabric motifs as a geometric learning context. The study was motivated by the low level of students’ HOTS achievement in mathematics and the limited research examining students’ higher-order thinking processes through local cultural contexts. This research employed a descriptive qualitative approach with a case study design involving nine ninth-grade students at a junior high school in Gowa Regency. Data were collected through analysis of students’ written responses to four worksheet activities, classroom observations, and learning documentation. The instruments included ethnomathematics-based worksheets, observation guidelines, and a HOTS assessment rubric measuring analysis, evaluation, and creation skills. The findings indicate varied levels of HOTS: three students were categorized as high, four as moderate, and two as low. High-category students demonstrated the ability to identify geometric elements, analyze patterns, and provide logical mathematical justifications. In contrast, moderate and low-category students experienced difficulties in connecting cultural patterns with geometric concepts and in developing appropriate solution strategies. The novelty of this study lies in its in-depth analysis of students’ HOTS thinking processes through the integration of local woven fabric motifs as an ethnomathematical context in geometry worksheets. The results imply that while ethnomathematics-based worksheets can stimulate higher-order thinking, their effectiveness depends on students’ conceptual readiness. Therefore, teachers should combine cultural contexts with structured conceptual reinforcement to ensure more equitable HOTS development